Advanced Optical Methods for Brain Imaging - Kao, Fu-Jen; Keiser, Gerd; Gogoi, Ankur (Progress in Optical Science and Photonics, 2019)
This book highlights the rapidly developing field of advanced optical methods for structural and functional brain imaging. As is known, the brain is the most poorly understood organ of a living body. It is indeed the most complex structure in the known universe and, thus, mapping of the brain has become one of the most exciting frontlines of contemporary research. Starting from the fundamentals of the brain, neurons and synapses, this book presents a streamlined and focused coverage of the core principles, theoretical and experimental approaches, and state-of-the-art applications of most of the currently used imaging methods in brain research. It presents contributions from international leaders on different photonics-based brain imaging modalities and techniques. Included are comprehensive descriptions of many of the technology driven spectacular advances made over the past few years that have allowed novel insights of the structural and functional details of neurons. The bookis targeted at researchers, engineers and scientists who are working in the field of brain imaging, neuroscience and connectomics. Although this book is not intended to serve as a textbook, it will appeal to undergraduate students engaged in the specialization of brain imaging.